Pelatihan Penggunaan Teknologi Informasi Untuk Meningkatkan Efisiensi Kerja Perawat di Kabupaten Pangkep - Malaha, Naomi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The advancement of information technology (IT) has had a significant impact on the world of nursing, especially in terms of documentation, communication, and work efficiency. However, the use of IT by nursing staff in areas such as Pangkep Regency is still limited due to the lack of adequate training and infrastructure. This community service activity aims to improve the understanding and skills of nurses in using information technology through direct, applicable training. Training methods include lectures, simulations, practice using the Hospital Management Information System (SIMRS), and evaluation through pre-tests and post-tests. The results of the activity showed a significant increase in the knowledge and skills of participants. The average participant score increased by 38 points after the training, and most participants felt that the training was very useful in supporting their work efficiency. In conclusion, IT training has proven to be effective as a strategy for increasing the capacity of nurses, and needs to be continued sustainably with adequate infrastructure support.